Áras an Uachtaráin (1962)
Josephine and Florence standing outdoors.
Keywords: O'Donoghue, Florence, -- 1895-1967; O'Donoghue, Josephine, -- 1891-1966; Ireland -- History -- 1922-; Photographic prints -- Irish -- 1960-1970